1993
DOI: 10.1007/bf01309663
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effect of dextran sulfate on the fusion and the in vitro replication of influenza A and B, Semliki Forest, vesicular stomatitis, rabies, Sendai, and mumps virus

Abstract: The effect of dextran sulfate on the fusion of a series of enveloped viruses, bearing specifically different fusion proteins, was investigated. The fusion with model- and with biological membranes was monitored by an R18 fluorescence-dequenching fusion assay. Dextran sulfate strongly suppresses the fusion of orthomxyo- (influenza A (H1N1 and H3N2 subtypes) and influenza B), of toga- (Semliki Forest virus), and of rhabdoviruses (vesicular stomatitis and rabies virus). The fusion of the paramyxo-viruses Sendai a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
3
14
1
Order By: Relevance
“…However, there are few studies on the role of the negative electric charge of DS in the DS-dependent suppression of influenza virus replication. DS was previously shown by direct binding experiments with FITC-labeled DS to bind to the viral membrane glycoproteins of influenza viruses (Lüscher-Mattli et al, 1993). We previously showed that the suppression of PR8 viral replication by DS was neutralized dose-dependently by adding diethylaminoethyl-dextran, a positively charged dextran (Yamada et al, 2012).…”
Section: Electrostatic Surface Potentials Of Nasmentioning
confidence: 97%
See 3 more Smart Citations
“…However, there are few studies on the role of the negative electric charge of DS in the DS-dependent suppression of influenza virus replication. DS was previously shown by direct binding experiments with FITC-labeled DS to bind to the viral membrane glycoproteins of influenza viruses (Lüscher-Mattli et al, 1993). We previously showed that the suppression of PR8 viral replication by DS was neutralized dose-dependently by adding diethylaminoethyl-dextran, a positively charged dextran (Yamada et al, 2012).…”
Section: Electrostatic Surface Potentials Of Nasmentioning
confidence: 97%
“…They also suggested that another binding site within the pocket formed by the 430-loop could be accessed by the new inhibitors. Novel antiviral compounds were identified which targeted the catalytic cavity as well as the 150-and 430-loops and which exhibit dynamic properties in electrostatic surface and geometric shape (Cheng et al, (De Clercq, 1986;Baba et al, 1988;Lüscher-Mattli et al, 1993). Some reports indicate that the negative charge of DS is associated with this inhibition.…”
Section: Electrostatic Surface Potentials Of Nasmentioning
confidence: 97%
See 2 more Smart Citations
“…These experiments indicate that proteins on the target cell surface are required both for cell-cell fusion and for pseudotype infection mediated by EboV GP. Similarly, incubation of HeLa-P4 target cells with dextran sulfate (100 or 500 g/ml; 120 min), a glucidic macromolecule interacting with glycosaminoglycans and inhibiting infection by various types of viruses (18,22), resulted in decreased efficiency of fusion with cells expressing EboV GP (Fig. 4A).…”
Section: Effects Of Target Cell Treatmentmentioning
confidence: 99%